Implementation of The Minister of Education, Culture, Research, and Technology’s Regulation No. 17 of 2021 Concerning National Assessment in Labuhan Batu State Elementary School - Napitupulu, Yuyun Anggia Murni; Warijo, Warijo; Adam, Adam (PERSPEKTIF, 2024)
Minister of Education, Culture, Research, and Technology Regulation Number 17 of 2021 concerning National Assessment has become the main focus in improving the quality of education in Indonesia. This research aims to examine the implementation of these regulations by conducting a case study at Labuhan Batu State Elementary School. The research method used is descriptive-qualitative, with data collection techniques through observation, interviews, and documentation. The research results show that the implementation of the Ministerial Regulation at the Labuhan Batu State Elementary School has had a positive impact on the national assessment process. Teachers have been able to understand the national assessment guidelines better and integrate them into the school curriculum. Apart from that, the implementation of this regulation also increases awareness of the importance of assessment in improving the quality of learning and evaluation. However, challenges such as the availability of resources and a deep understanding of assessment concepts are still obstacles. This research provides an important contribution to understanding the implementation of Minister of Education Regulation Number 17 of 2021 at the elementary school level, as well as providing input for related parties in efforts to increase the effectiveness of national assessments in the future.